Bone and Joint Infections due to Haemophilus parainfluenzae: Case Report and Review of the Literature - Conar R. O’Neil; Evan Wilson; Bayan Missaghi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Haemophilus parainfluenzae is a normal inhabitant of the human respiratory tract. However it is an increasingly recognized pathogen in invasive infections, particularly in the immunocompromised host and where there is disruption of the normal skin or mucosal barriers. We present a case of a 56-year-old female with a history of asplenia who developed H. parainfluenzae septic arthritis of the hip following an intra-articular steroid injection. We also summarize previously reported cases of bone and joint infections caused by H. parainfluenzae.